A comparison of the rheological behavior of hydrate forming emulsions stabilized using either solid particles or a surfactant. (1st September 2016) - Yegya Raman, Ashwin Kumar; Koteeswaran, Samyukta; Venkataramani, Deepika; Clark, Peter; Bhagwat, Swanand; Aichele, Clint P.
Abstract: Simple clathrate hydrates are non-stoichiometric, ice-like crystalline compounds that can, among other things, cause blockages of oil and gas pipelines. More challenging exploration and development has emphasized the need to investigate the rheological behavior of hydrates in order to ensure continuous production of crude oil through pipelines especially for solid stabilized emulsions. Therefore, a difference in the rheological behavior of hydrate forming water-in-oil emulsions stabilized using either solid particles (Aerosil R974, fumed silica particles) or a surfactant (Span 80, a non-ionic surfactant) over a range of water cuts is investigated. A rheometer with helical ribbon geometry was used to investigate the rheological behavior of hydrate slurries as opposed to conventional standard geometries. Cyclopentane was used as the hydrate-forming component. The results showed that hydrate formation was rapid in the presence of solid particles compared to surfactant. We hypothesize that solid particles act as nucleation sites and reduce the induction time required for hydrate formation. In addition, the viscosity of water-in-oil emulsions increased with an increase in water cut. Hydrate forming emulsions formed using solid particles had a higher viscosity than emulsions formed using surfactant.